Caracas, Departure City: Urban planning after emigration and collapse - Gzyl, Stefan (AESOP, 2024)
The recent deterioration of living conditions in Venezuela has resulted in an unprecedented migratory crisis, infrastructure collapse, and institutional decline. In the middle of this complex situation, migrants’ left-behind properties are being transformed into new uses. These changes often contradict zoning regulations, prompting a series of legal, social, and spatial strategies to conceal them. This article examines ongoing spatial and programmatic transformations of vacant homes in Caracas, the country’s capital, framing these changes within disciplinary discourses of shrinking and departure cities and in a specific experience of collapse that shapes daily life in the city. The article studies spatial transformations in terms of their material conditions and the opaque and informal procedures that produce them, describing the process from the point of view of various actors, from architects and entrepreneurs to local residents and planning authorities. Through interviews, site visits, and photographic documentation, the article describes the challenges and possibilities for social organization and institutional renovation in a climate of emigration and uncertainty.
Gzyl, S. (2024). Caracas, departure city: Urban planning after emigration and collapse. plaNext – Next Generation Planning, 14, 114–130. https://doi.org/10.24306/plnxt/95